HUBUNGAN MOTIVASI BERPRESTASI DAN DISIPLIN DENGAN KINERJA DOSEN - Sulastri, Tuti (Fakultas Ekonomi Universitas Islam 45, 2007)
Our research has been done for 3 months with 60 lecturers as the object In the research we want to know the relationship among motivation to achievement, discipline and performance as a lecturer at Universitas Islam 45 (Unisma) Bekasi, With regard to that, the hypothesis of the research is motivation to achievement and discipline has significant correlation to lecturer performance, We use regression test analysis and the result are: a) There is a positive correlation between motivation to achievement and lecturers performance with correlation coefficient y y,l= 0,650, b) There is a positive correlation between discipline and lecturers performance with correlation coefficient yy.2 = 0,615 and c) There is a positive correlation among motivation to achievement, discipline and lecturer performance with correlation coefficient 9? y.1.2 = 0,690L The result of F test with significance rate 0,05 are: a) Motivation to achievement variables influence on lecturers performance 42,25 %, b) Discipline variables influence on lecturer performance 37,82 % and c) Motivation to achievement and discipline variables influence on lecturers performance 47,61 %, Lecturer performance as education staff at Unisma is influenced on motivation to achievement higher than discipline.